Pemanfaatan Artificial Intelligence dalam Deteksi dan Pencegahan Tindak Pidana Pencucian Uang: Potensi dan Tantangan Hukum? - Febriyani, Emiliya; Syarief, Elza; Seroja, Triana Dewi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
Artificial Intelligence (AI) is one of the leading technologies that has begun to attract attention in the financial sector across various regions worldwide, including Southeast Asia. One potential application of AI is its ability to automatically detect specific data or situations within an electronic system, which can be utilized to identify money laundering activities. However, this cutting-edge technology may also result in certain unintended legal implications. The purpose of this study is to explore the potential and legal challenges in utilizing AI for the detection and prevention of money laundering. This research employs a normative legal research method to examine the legal implications of AI utilization in efforts to prevent and combat money laundering. The analysis reveals that significant normative issues persist regarding the legal certainty of AI applications in general, which poses complex challenges when coupled with specific legal implications, such as consumer protection and the safeguarding of privacy and data rights. This study proposes a legal development model that emphasizes balancing the efforts to prevent and combat money laundering with the rights of financial service users to maintain the integrity of the financial system.